Literature Review: Investasi Syariah Sukuk Ritel - Siti Ruhana Dara (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
Abstract: Sukuk are sharia bonds that the Indonesian government offers to Indonesian citizens in two forms, Sukuk Ritel and sukuk tabungan. Retail Sukuk has different characteristics from Savings Sukuk including the provision of Coupons, trading in the secondary market, potential capital gains, and tenors. Government Sukuk is an investment instrument that can be an option because the risk is small, since the government issued Sukuk, both Savings and Retail, there has never been a default either for the coupon or for the nominal value, and also the sukuk has a coupon rate which tends to be higher than bank deposits. Potential for capital gains, retail sukuk have the potential profits because they can be traded on the secondary market and have the potential to increase bond prices, while savings sukuk have no potential for capital gains because they cannot be traded on the secondary market. For the time or tenor of the sukuk, retail sukuk has 3 year tenor while savings bonds have 2 year tenor. Keywords: Retail Sukuk, Savings Sukuk, Outstanding, coupons Abstrak: Sukuk merupakan obligasi syariah yang pemerintah Indonesia tawarkan untuk warga Negara Indonesia dengan dua yaitu sukuk Ritel dan Sukuk Tabungan. Sukuk ritel memiliki karakteristik yang berbeda dengan sukuk tabungan diantaranya adalah pemberian Kupon, perdagangan di pasar sekunder, potensi capital gain, dan tenor. Sukuk Pemerintah adalah salah satu pilihan instrument investasi berbasis syariah yang bisa menjadi pilihan karena risikonya kecil, sejak pemerintah mengeluarkan Sukuk baik itu Tabungan maupun Ritel tidak pernah terjadi gagal bayar baik untuk kupon maupun untuk nlai nominalnya, dan juga sukuk memiliki tingkat kupon yang cenderung lebih besar dari Deposito perbankan. Potensi capital gain, sukuk ritel memiliki potensi mendapat keuntungan karena dapat diperdagangkan di pasar sekunder dan memiliki potensi kenaikan harga obligasi, sedangkan sukuk tabungan tidak memiliki potensi capital gain karena tidak dapat diperdagangkan di pasar sekunder. Untuk waktu atau tenor sukuk, sukuk ritel memiliki tenor 3 tahun sedangkan sukuk tabungan 2 tahun. Kata kunci: Sukuk Ritel, Sukuk Tabungan, Outstanding, kupon